2022
DOI: 10.3389/fendo.2022.800119
|View full text |Cite
|
Sign up to set email alerts
|

The Russian Registry of Chronic Hypoparathyroidism

Abstract: IntroductionChronic hypoparathyroidism is a relatively rare disease associated with multicomponent medical therapy and various complications. The analysis of large databases of patients with chronic hypoparathyroidism is a necessary tool to enhance quality of medical care, as well as to determine the optimal clinical and therapeutic approaches, and prognostic markers of the disease.The Aimof this study is to estimate the clinical and biochemical profile, long-term complications, medical therapy and disease con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
1
6
0
2
Order By: Relevance
“…Concerning possible diff erences between surgical and non-surgical cases we confi rmed the tendency for non-surgical patients to be younger and to present with deeper hypocalcemia and hypomagnesiemia. This fi nding has already been reported in previous studies by other authors [14,30]. The reasons behind these diff erences are not yet clearly elucidated but surely refer to the diff erent etiology of hypoPT (lack of parathyroid tissue versus autoimmune or invasive destruction of the parathyroid cells and secretion) [31].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Concerning possible diff erences between surgical and non-surgical cases we confi rmed the tendency for non-surgical patients to be younger and to present with deeper hypocalcemia and hypomagnesiemia. This fi nding has already been reported in previous studies by other authors [14,30]. The reasons behind these diff erences are not yet clearly elucidated but surely refer to the diff erent etiology of hypoPT (lack of parathyroid tissue versus autoimmune or invasive destruction of the parathyroid cells and secretion) [31].…”
Section: Discussionsupporting
confidence: 76%
“…At the same time hypercalciuria was relatively uncommon (in 11.8%). In other detailed studies the prevalence of renal stones had been reported as low as 32.5% [14] or even < 27% [15]. The detrimental impact of the hypoPT itself on the kidney has already been documented [23].…”
Section: Discussionmentioning
confidence: 94%
“…По данным анализа всероссийского регистра пациентов с гипопаратиреозом (n=544) отмечено, что нарушение функции почек со снижением СКФ менее 60 мл/мин/1,73 м 2 происходит в 15,8% случаев, нефролитиаз выявляется у 32,5% пациентов, нефрокальциноз -у 12,3%. Установлено, что уровень кальциемии имеет отрицательную корреляцию с рСКФ, а риски структурных нарушений почек повышаются с увеличением длительности заболевания более 4,5 года [16].…”
Section: Discussionunclassified
“…The skeletal consequences of chronic HypoPT conventionally treated with calcium supplements and active vitamin D are described below and summarized in Table 1. Bone remodeling Reduced • Bone turnover markers in the lower half of the normal range (12,16).…”
Section: Skeletal Consequences Of Hypoptmentioning
confidence: 99%
“…The bone formation markers procollagen type 1 amino-terminal propeptide, osteocalcin, and bone-specific alkaline phosphatase are decreased, along with reduced levels of the bone resorption markers serum C-telopeptide and tartrate-resistant acid phosphatase 5b ( 1 ). Of note, while histomorphometry of bone biopsies shows a marked reduction in bone remodeling, bone turnover markers are not frankly low but are usually in the lower half of the normal range ( 12 , 16 ), which limits their use in clinical practice to delineate the status of bone turnover in patients with HypoPT.…”
Section: Introductionmentioning
confidence: 99%